Representation of Icelandic-Basque contacts in a Finnish novel - Willson, Kendra (Det Kgl. Bibliotek/Royal Danish Library, 2025)
Finnish author Tapio Koivukari creates in his novel Ariasman(2011), based on a historical massacre of shipwrecked Basque whalers in Iceland in 1615, a literary representation of an extinct Icelandic Basque pidgin known from a few lists of words and phrases with roots in the seventeenth century. The brief dialoguesin the book given in Basque or pidgin draw on the word lists, knowledge of the modern languages, and Koivukari’s imagination. The pidgin phrases used in the book concentrate on a few semantic fields: domestic animals, food, clothing,religion and relationships, largely corresponding to those found in the glossaries. Icelandic names are adapted to Basque phonology and given Basque diminutive endings. Multilingual word play is exploited. Koivukari supplements thevocabulary attested in the word lists with words from modern Basque and other languages known to have been part of the contact situation. This article describes how the book extrapolates from the documented glossaries to create fictionaldialogues between Basque and Icelandic speakers, and more generally how itthematizes difficulties and strategies in communication, using imagination to flesh out the dynamics of the historical contact situation.